Broken Bodies, Places and Objects New Perspectives on Fragmentation in Archaeology - Sörman, Anna; Noterman, Astrid A.; Fjellström, Markus (Taylor & Francis, 2024)
Broken Bodies, Places and Objects demonstrates the breadth of fragmentation and fragment use in prehistory and history and provides an up-to-date insight into current archaeological thinking around the topic. A seal broken and shared by two trade parties, dog jaws accompanying the dead in Mesolithic burials, fragments of ancient warships commodified as souvenirs, parts of an ancient dynastic throne split up between different colonial collections... Pieces of the past are everywhere around us. Fragments have a special potential precisely because of their incomplete format - as a new matter that can reference its original whole but can also live on with new, unrelated meanings. Deliberate breakage of bodies, places and objects for the use of fragments has been attested from all time periods in the past. It has now been over 20 years since John Chapman's major publication introducing fragmentation studies, and the topic is more present than ever in archaeology. This volume offers the first European-wide review of the concept of fragmentation, collecting case studies from the Neolithic to Modernity and extending the ideas of fragmentation theory in new directions. The book is written for scholars and students in archaeology, but it is also relevant for neighbouring fields with an interest in material culture, such as anthropology, history, cultural heritage studies, museology, art and architecture.